Acid phosphatase activity distribution in salivary glands of triatomines (Heteroptera, Reduviidae, Triatominae) - Anhe, A. C. B. [UNESP]; Oliveira, A. P. M. Lima [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Funpec-editora, 2007)
Acid phosphatase activity (Gomori technique) in salivary gland cells was investigated in adult insects (males and females) of four species of triatomines: Triatoma infestans, Panstrongylus megistus, Rhodnius neglectus, and Rhodnius prolixus. Binucleated cells with bulky and polyploidy nuclei were detected, with acid phosphatase activity in the heterochromatin and nucleolus, which showed the most intense response. Thus, the activity of these phosphatases during rRNA molecule transcription, possibly in the nucleolar fibrillar center, is suggested. The difference in reactivity found among salivary glands is associated with the cellular metabolism of these regions and, probably, with the biosynthesis of their different secretions. This must be essential in maintaining the hematophagy of triatomines.
Keywords: Acid phosphatase; salivary gland; nucleolus; Triatominae; Heteroptera